(untitled) (Journal of Social Sciences Review, 2023)
Despite existing studies on negative consumer-brand relationships, understanding of extreme negative states, such as brand betrayal and brand hate, is still in the infancy stage. The current study addresses this crucial gap by investigating the effect of brand betrayal on brand hate and subsequent consumer behaviors. Specifically, it examines the effect of two different forms of betrayal (i.e., performance versus value-based betrayal) in influencing brand hate and unfavorable consumer behaviors (i.e., vindictive complaining and boycotting). The study respondents were recruited and surveyed online via Prolific. The sample included 391 responses which were further divided into two groups, i.e., one who suffered from performance-based betrayal and the other from value-based betrayal. The findings reveal a significant positive association of brand betrayal with brand hate, vindictive complaining, and consumer boycott. Interestingly, the magnitude of the effects of value-based brand betrayal is greater than that of performance-based betrayal. Moreover, brand hate is significantly associated with vindictive complaining and consumer boycotts. The findings enrich negative consumer-brand relationship literature and provide managerial guidance for devising effective strategies for brand transgressions.